2018
DOI: 10.1016/j.physd.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

4-wave dynamics in kinetic wave turbulence

Abstract: h i g h l i g h t s• We deal with 4-wave Hamiltonian systems in the framework of wave turbulence.• Averaging technique based on the Feynman-Wyld diagrams.• Kinetic limit : leading order equations for the statistics evolution are derived.• Random-phase and random-phase and amplitude properties preserved in time.• Powerful tool to investigate many relevant physical systems. Keywords: Weak wave turbulence Kinetic theory Intermittency a b s t r a c tA general Hamiltonian wave system with quartic resonances is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…We remark in this respect that the key assumption underlying the wave turbulence approach is the existence of a random phase among the modes rather than a genuine Gaussian statistics, as recently discussed in detail in Refs. [7,86,87]. We emphasize that in the present work the random phase of the modes is induced by the structural disorder of the medium that dominates nonlinear effects (L d L nl ).…”
Section: Closure Of the Moments Equationsmentioning
confidence: 80%
See 2 more Smart Citations
“…We remark in this respect that the key assumption underlying the wave turbulence approach is the existence of a random phase among the modes rather than a genuine Gaussian statistics, as recently discussed in detail in Refs. [7,86,87]. We emphasize that in the present work the random phase of the modes is induced by the structural disorder of the medium that dominates nonlinear effects (L d L nl ).…”
Section: Closure Of the Moments Equationsmentioning
confidence: 80%
“…Also note that we have deliberately chosen a small value of the condensate fraction n 0 /N 0.2 so as to avoid large deviations from Gaussianity for the fundamental mode -though the the- ory has been validated even for large condensate fractions in [41]. We recall here the recent works showing that a key assumption of the wave turbulence approach is the existence of a random phase among the modes rather than a genuine Gaussian statistics [86,87].…”
Section: Acceleration Of Thermalization Mediated By Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent works, however, it has been shown that the quasi-Gaussian assumption can be dropped, and the WKE can be derived instead assuming random phases and amplitudes (Choi, Lvov & Nazarenko 2005 a ; Choi et al. 2005 b ; Eyink & Shi 2012; Chibbaro, Dematteis & Rondoni 2018). Depending on different methods of the derivation, takes the form of (Zakharov et al.…”
Section: Formulation Of Energy Flux For the Mmt Modelmentioning
confidence: 99%
“…is the wave action spectral density, and • is performed over the initial random phases and independent actions. Strictly speaking, the WK equation is valid under the assumption that random phases and amplitudes persist over time [41]. Besides the evolution equation for the spectral density function, using the same approximations and tools, it is also possible to derive an evolution equation for the second moment, Λ k = I 2 k (M/2π) 2 , which reads:…”
Section: Introductionmentioning
confidence: 99%